Marine Mesozoic Rocks in Mae Hong Son Province, Thailand: Paleoenvironmental and Tectonic Setting Implications - Paweena Seedee (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The Marine Mesozoic rocks in this study are distributed in northern Part of Mae Hong Son Province. Three localities of chert sections have been investigated for paleoenvironmental and tectonic setting implications. This study focused on micropaleontology, chronostratigraphy, petrography and geochemistry of cherts in order to determine the youngest age range of the Main Paleo-Tethys. Chert samples were radiolarian extracted and systematically studied. These samples contain poor to rich identifiable radiolarian fauna. Radiolarians are composed of 13 families, 18 genera and 28 species. This study can be divided into six assemblage zones: 1) Ishigaum trifustis Assemblage (Wuchiapingian) 2) Albaillella excelsa Assemblage (Wuchiapingian-Changhsingian) 3) Spumellaria Assemblage (Olenekian-Anisian) 4) Triassocampe deweveri Assemblage (Ladinian) 5) Capnuchosphaera-Triassocampe sp. Assemblage (Carnian) 6) Spongostylus tortilis Assemblage (late Carnian - early Norian?) in chronological order. These assemblages are correlated with previous works. According to radiolarian data, the sequences of cherts span from Late Permian to Late Triassic (Wuchuapiangian to late Carnian). Therefore, the youngest age of chert in this study is considered to be the Late Triassic (late Carnian), approximately 228 Ma, which implies the latest timing of closure of the Paleo-Tethys. For petrographic study, most chert in this study comprised microcrystalline, clay minerals, organic matters, fauna and quartz vein. These chert were deposited in deep ocean basin environment which is below the carbonate compensation depth (CCD), approximately deeper than 4 km. Chert characteristics are accumulated in a low energy environment. For geochemical study, twenty three chert samples were analyzed by using X-Ray Fluorescence (XRF) methodology for major and trace elements analysis. The analyzed samples have high silica content (89 percent average). These rocks, also called biogenical sediments, were originated from siliceous test and sponge spicules. Some samples have a few terrigenous input and were influenced by hydrothermal input. Moreover, the result indicated that chert sequences in this study were deposited near the continental margin and were not affected by volcanic and weathering contribution.